2022
DOI: 10.1111/nph.17928
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of global change on the phyllosphere microbiome

Abstract: Summary Plants form complex interaction networks with diverse microbiomes in the environment, and the intricate interplay between plants and their associated microbiomes can greatly influence ecosystem processes and functions. The phyllosphere, the aerial part of the plant, provides a unique habitat for diverse microbes, and in return the phyllosphere microbiome greatly affects plant performance. As an open system, the phyllosphere is subjected to environmental perturbations, including global change, which wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 127 publications
2
64
0
1
Order By: Relevance
“…Microbes are abundant and diverse in mountain regions, play an essential role in virtually all biogeochemical cycling processes and are an important component of ecosystem response to global change (Battin et al ., 2016; Cavicchioli et al ., 2019; Zhu et al ., 2022). Mountains offer contrasting ecosystem types and continuous environmental gradients for their biota (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes are abundant and diverse in mountain regions, play an essential role in virtually all biogeochemical cycling processes and are an important component of ecosystem response to global change (Battin et al ., 2016; Cavicchioli et al ., 2019; Zhu et al ., 2022). Mountains offer contrasting ecosystem types and continuous environmental gradients for their biota (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have demonstrated that the phyllosphere harbors diverse microbial communities that in uenced ecosystem functioning [14][15][16][17][18][19]. Recent studies stress the importance of understanding the mechanisms underlying how plant-microbe interactions in the phyllosphere could in uence host survival and tness in the context of global change [20,21]. Several studies have illustrated that host genotypes can in uence the composition of the leaf microbiome [22][23][24], but little is clear how the plant shapes its leaf microbiota and how the leaf microbiome contributes to plant phenotypic traits [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have demonstrated that the phyllosphere harbors diverse microbial communities that influenced ecosystem functioning (14)(15)(16)(17)(18)(19). Recent studies stress the importance of understanding the mechanisms underlying how plant-microbe interactions in the phyllosphere could influence host survival and fitness in the context of global change (20,21). Several studies have illustrated that host genotypes can influence the composition of the leaf microbiome (22)(23)(24), but little is clear how the plant shapes its leaf microbiota and how the leaf microbiome contributes to plant phenotypic traits (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%